2016
DOI: 10.1007/s00204-016-1687-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles for calcium-sensing receptor (CaSR) and transient receptor potential ankyrin-1 (TRPA1) in murine anorectic response to deoxynivalenol (vomitoxin)

Abstract: Food contamination by the trichothecene mycotoxin deoxynivalenol (DON, vomitoxin) has the potential to adversely affect animal and human health by suppressing food intake and impairing growth. In mice, the DON-induced anorectic response results from aberrant satiety hormone secretion by enteroendocrine cells (EECs) of the gastrointestinal tract. Recent in vitro studies in the murine STC-1 EEC model have linked DON-induced satiety hormone secretion to activation of calcium-sensing receptor (CaSR), a G-coupled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…The CaSR may also exert these anorectic effects by increasing the secretion of GLP-1210, which in turn suppresses appetite following food ingestion, as well as by increasing CCK secretion from I-cells220, that leads to a delay in gastric emptying. CaSR activation may also cause emesis and studies involving mice have demonstrated that deoxynivalenol, which is an emesis-inducing toxin, acts by increasing CaSR-mediated secretion of CCK and PYY221. These findings may potentially explain the GI adverse effects such as nausea and vomiting, which are experienced by >30% of patients being treated with cinacalcet, which is used for pharmacological activation of the CaSR 146.…”
Section: Non-calcitropic Roles Of the Casrmentioning
confidence: 99%
“…The CaSR may also exert these anorectic effects by increasing the secretion of GLP-1210, which in turn suppresses appetite following food ingestion, as well as by increasing CCK secretion from I-cells220, that leads to a delay in gastric emptying. CaSR activation may also cause emesis and studies involving mice have demonstrated that deoxynivalenol, which is an emesis-inducing toxin, acts by increasing CaSR-mediated secretion of CCK and PYY221. These findings may potentially explain the GI adverse effects such as nausea and vomiting, which are experienced by >30% of patients being treated with cinacalcet, which is used for pharmacological activation of the CaSR 146.…”
Section: Non-calcitropic Roles Of the Casrmentioning
confidence: 99%
“…Loss of appetite is common [46] and may be severe in COVID- 19. It has been suggested that TRPA1 may play a role in food intake and satiety [47][48][49][50]. In animals, TRPA1 activation increases appetite [51].…”
Section: Covid-19 Symptomsmentioning
confidence: 99%
“…The frequent contamination of wheat with the fungi Fusarium leads to food contamination by trichothecene mycotoxin deoxynivalenol (DON, vomitoxin) [ 109 ]. DON suppresses food intake and thereby affects energy balance, which is a major concern in human and animal health.…”
Section: Organ-specific Expression Of Chemosensing and Sensory Trpmentioning
confidence: 99%
“…The exocytosis of satiety hormones like cholecystokinin and peptide YY 3–36 is induced by DON-activated calcium-sensing receptor (CaSR) and TRPA1-mediated Ca 2+ entry into enteroendocrine cells [ 110 ]. Further analysis of the role of CaSR and TRPA1 in the observed anorexia and emesis will shed light on the underlying mechanisms, and can therefore serve as a model to understand comparable symptoms induced by other foodborne toxins, environmental toxicants and chemotherapeutic drugs [ 109 ].…”
Section: Organ-specific Expression Of Chemosensing and Sensory Trpmentioning
confidence: 99%